Methodology of organizing music lessons in 5-7 grades of general secondary schools based on new technologies - Abdumutalibovich, Ma’rufjon Ashurov (Journal of Learning on History and Social Sciences, 2024)
In this article, the methodology of the music teacher's organization of music lessons in the 5th-7th grades of general secondary schools on the basis of new technologies is explained.